A photogrametric study on active faults in the Nepal Himalayas - Nakata, Takashi (Journal of Nepal Geological Society, 1982)
Active faults in the Nepal Himalayas are identified by means of interpretation of vertical aerial photographs. They are mainly distributed along the major tectonic lines as older geological faults and are classified into four groups, the Main Central Active Fault system, the active faults in the Lower Himalayas, the Main Boundary Active Fault system and active faults along the Himalayan Front Fault. The mode of active faulting is closely related to the strikes of the faults. Along the NW-SE and NE-SW trending faults, lateral displacement with northward drop is prevailing, and right-lateral movement along the former and left-lateral movement along the latter is a rule in the sense of displacements. On the other hand, dip-slip faulting is observed mainly along the E-W trending faults belonging to the Main Boundary Active Fault system. However, apparent displacement along the faults is mostly of northward drop. It is considered that active faulting along the major tectonic lines except the Himalayan Front Fault does not favor the upheaval of the Himalayan ranges during the late Quaternary period.